STRATEGI PROMOSI DENGAN MEMANFAATKAN MEDIA SOSIAL TIKTOK DALAM MENINGKATKAN PENJUALAN (Studi Kasus Pada TN Official Store) - Hayatun Nufus; Trisni Handayani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
This study aims to find out what factors make the TikTok platform an effective promotional media in marketing a product and increasing sales. In this study the method used is a descriptive approach, this research is a field research, the data used from this study are primary and secondary data, with observation data collection techniques, and interviews. The results showed that sales promotion by giving discounts or price reductions, giving vouchers and coupons, free bars and product guarantees. Publicity with a direct approach to consumers. Interactive marketing by involving consumers in sales activities. TikTok with various interesting features in it. These things help TN Official Store to market their products and increase their sales. So optimal use of TikTok features and a good relationship with consumers can help increase sales. Thus, TikTok becomes an effective promotional media in marketing activities.